Atorvastatin Decreased Circulating RANTES Levels in Impaired Glucose Tolerance Patients with Hypercholesterolemia: An Interventional Study - Feng, Xiaomeng (Diabetes Ther, 2017)
INTRODUCTION: Impaired glucose tolerance (IGT) is the major cause of the development of both type 2 diabetes and atherosclerosis. Regulated upon activation, normal T cells expressed and secreted (RANTES), a proinflammatory chemokine, is associated with atherosclerosis. We investigated the effect of atorvastatin on circulating RANTES in IGT patients with hypercholesterolemia. METHODS: This study evaluated cross-sectional and interventional studies of 32 IGT patients with hypercholesterolemia (group A) and 32 controls (group B). Group A was treated with atorvastatin (20 mg/day) for 8 weeks. Platelet-free plasma (PFP) RANTES and clinical characteristics were examined. RESULTS: PFP RANTES was significantly higher in group A compared with group B (9.76 ± 3.10 vs 6.43 ± 2.16 ng/ml, P < 0.001). PFP RANTES was positively correlated with total cholesterol (TC) (r = 0.589, P < 0.001), low-density lipoprotein cholesterol (LDL-C) (r = 0.583, P < 0.001), triglycerides (TG) (r = 0.450, P < 0.001), fasting blood glucose (FBG) (r = 0.469, P < 0.001), 2-hour postchallenge glucose (2hPG) (r = 0.397, P = 0.001), glycosylated hemoglobin (HbA1c) (r = 0.353, P = 0.004), and high sensitivity C-reactive protein (hsCRP) (r = 0.616, P < 0.001), and negatively related to high-density lipoprotein cholesterol (HDL-C) (r = −0.272, P = 0.029). After controlling for confounders, LDL-C (β = 2.109, P < 0.001) and hsCRP (β = 0.272, P = 0.029) were independently related to RANTES. After atorvastatin treatment, PFP RANTES significantly decreased in group A compared with baseline (from 9.76 ± 3.10 to 7.48 ± 2.78 ng/ml, P < 0.001). CONCLUSIONS: Atorvastatin decreased circulating RANTES in IGT patients with hypercholesterolemia, indicating that statins may play an important role in inhibiting inflammatory responses in patients with IGT.